Clinical Etiology of Optic Neuropathy patients visiting BPKLCOS, Institute of Medicine, Nepal - Yadav, Amit Kumar; Sitaula, Sanjeeta; Joshi, Sagun Narayan; Sharma, Ananda Kumar (Janaki Medical College Journal of Medical Science, 2023)
Background & Objective: The clinical etiology of Optic neuropathy is vast and may be associated with life threatening conditions which might demand initiation of treatment. Therefore, the aim of the study was to evaluate clinical etiology among patients visiting ophthalmology OPD of Institute of medicine, Nepal. Material and Methods: This is a descriptive study conducted at B.P. Koirala Lions Centre for Ophthalmic Studies, Institute of Medicine, Nepal. All cases of optic neuropathy who presented to outpatient department (OPD), indoor patients from 7th July 2017-6th July 2018 were included in the study. A detailed clinical history was obtained which was followed by ophthalmic examination and relevant investigation. In addition, assessment of visual acuity, color vision, contrast sensitivity, visual field were done. Data was analyzed with SPSS version 24. Results: A total of 86 eyes of 66 patients with optic neuropathy meeting all the inclusion criteria during the study period were enrolled with 20 patients having bilateral eye involvement and 46 having unilateral eye involvement accounting for a total of 86 eyes with optic neuropathy. The mean age of the affected population was 39.12±13.57 years with male to female ratio of 1:1.1. The most common etiology for optic neuropathy was optic neuritis (n=40 patients, 60.6%). Diminution of vision was the most common presenting complaints. Best corrected visual acuity was 6/24 –6/60 in 39.5% cases (n=34). Majority of the eyes had presence of RAPD (n=53 eyes, 61.7%) The most common color vision defect was nonspecific defect (n=41eyes, 47.7%).There was reduced contrast in 55.8% of the affected eyes in cases of optic neuropathy. Majority of affected eyes had blurred disc margin (n=39 eyes, 45.3%) followed by hyperemic disc and pale disc. Majority of the patients could not perform visual field due to low vision but those who could perform had enlarged blind spot. Conclusion: The most frequent etiological factor for optic neuropathy was optic neuritis. In cases of optic neuropathy, the main complaint of the majority of patients was a dimunition in vision. The majority of cases of optic neuropathy involved abnormalities in both colour vision and contrast sensitivity. The most typical visual field pattern in eyes with optic neuropathy was an enlarged blind spot. Optic neuritis is the most common cause of optic neuropathy, followed by traumatic optic neuropathy, and toxic metabolic optic neuropathy.